Neuroscience, Neurophysiology and Symmetry - Paillard, Thierry; Singh, Sandeep (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint focuses on fundamental and applied research on asymmetry of movement and postural balance and underlying functions in humans. Experimental protocols based on kinetic, kinematic, radiological, functional magnetic resonance imaging and transcranial Doppler ultrasound data taken from healthy, young, elderly and pathological individuals provide new insights into asymmetry in human movement and posture and are presented in the Special Issue.